m6A potentiates Sxl alternative pre-mRNA splicing for robust Drosophila sex determination - Haussmann, Irmgard U.; Bodi, Zsuzsanna; Sanchez-Moran, Eugenio; Mongan, Nigel P.; Archer, Nathan; Fray, Rupert G.; Soller, Matthias (Nature Publishing Group, 2016)
N6-methyladenosine (m6A) is the most common internal modification of eukaryotic messenger RNA (mRNA) and is decoded by YTH domain proteins1, 2, 3, 4, 5, 6, 7. The mammalian mRNA m6A methylosome is a complex of nuclear proteins that includes METTL3 (methyltransferase-like 3), METTL14, WTAP (Wilms tumour 1-associated protein) and KIAA1429. Drosophila has corresponding homologues named Ime4 and KAR4 (Inducer of meiosis 4 and Karyogamy protein 4), and Female-lethal (2)d (Fl(2)d) and Virilizer (Vir)8, 9, 10, 11, 12. In Drosophila, fl(2)d and vir are required for sex-dependent regulation of alternative splicing of the sex determination factor Sex lethal (Sxl)13. However, the functions of m6A in introns in the regulation of alternative splicing remain uncertain3. Here we show that m6A is absent in the mRNA of Drosophila lacking Ime4. In contrast to mouse and plant knockout models5, 7, 14, Drosophila Ime4-null mutants remain viable, though flightless, and show a sex bias towards maleness. This is because m6A is required for female-specific alternative splicing of Sxl, which determines female physiognomy, but also translationally represses male-specific lethal 2 (msl-2) to prevent dosage compensation in females. We further show that the m6A reader protein YT521-B decodes m6A in the sex-specifically spliced intron of Sxl, as its absence phenocopies Ime4 mutants. Loss of m6A also affects alternative splicing of additional genes, predominantly in the 5′ untranslated region, and has global effects on the expression of metabolic genes. The requirement of m6A and its reader YT521-B for female-specific Sxl alternative splicing reveals that this hitherto enigmatic mRNA modification constitutes an ancient and specific mechanism to adjust levels of gene expression.